SEDATIVE & ANTIANXIETY ACTIVITY OF ETHANOLIC EXTRACT OF ECLIPTA ALBA IN ALBINO RATS - MONALISA JENA,; SWATI MISHRA, (International Journal of Pharma and Bio Sciences, 2013)
Anxiety is a most common emotional disorder affecting 20% of adult population worldwide. Eclipta alba is having memory enhancing quality & traditionally used for this purpose. Since paucity of data available for this clinical use, the present work was undertaken to study the anti anxiety & sedative effects of Ethanolic extract of leaves of Eclipta alba(EEEA) in albino rats using thiopental sodium induced sleeping time (TIS), locomotor activity by actophotometer, elevated plus maze test( EPM ).EEEA was administered in 50,100,200&400mg/kg doses PO. In the TIS time, the extract in a dose of 200 & 400 mg/kg induced the sleep at an earlier stage & prolonged the duration of sleep. The extract at the dose of 400mg increased % of entries & time spent in the open arms significantly. The EEEA also decreased the locomotor activity in the same dose. The EEEA was found to possess both sedative & anxiolytic activity.